2018
DOI: 10.1002/ss.20260
|View full text |Cite
|
Sign up to set email alerts
|

Code‐Switching to Navigate Social Class in Higher Education and Student Affairs

Abstract: This chapter outlines the concepts of social class privilege, highlights the experiences of students navigating social class, and examines the role of code‐switching as a strategy to navigate higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…BIPOC scholars feel the need to ‘shapeshift’ between their professional and casual selves to maintain their personal sanity and peace within the workplace and to fit into the culture of the academic environment, which may be predominantly influenced by the cultural norms and expectations of the white middle class ( Richardson, 2019 ). Moreover, BIPOC scholars often alter their appearance, vernacular, and various other elements of their being to contradict the negative stereotypes often placed on Black people ( Elkins & Hanke, 2018 ). This duality in addition to other social factors contribute to BIPOC scholars reporting more occupational stress than their white peers ( Hall et al., 2012 ; Wadsworth et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…BIPOC scholars feel the need to ‘shapeshift’ between their professional and casual selves to maintain their personal sanity and peace within the workplace and to fit into the culture of the academic environment, which may be predominantly influenced by the cultural norms and expectations of the white middle class ( Richardson, 2019 ). Moreover, BIPOC scholars often alter their appearance, vernacular, and various other elements of their being to contradict the negative stereotypes often placed on Black people ( Elkins & Hanke, 2018 ). This duality in addition to other social factors contribute to BIPOC scholars reporting more occupational stress than their white peers ( Hall et al., 2012 ; Wadsworth et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Challenges from low-income students who do not have knowledgeable translators in their lives are exacerbated in an asynchronous online course where instructor or peer responses to students' questions are not instantaneous. Elkins and Hanke (2018) reported that lowincome students practice "code switching," in which they change the way they speak when they are at a higher education institution versus when they are at home, to fit in.…”
Section: Low Income Studentsmentioning
confidence: 99%
“…Research suggests students from working‐class backgrounds are constantly aware of material differences between themselves and their peers (Martin, 2015), which can impact much of their college experience. Students employ strategies to navigate cross‐class differences; one such strategy is code switching, whereby “individuals choose their styles of communication, both verbal and nonverbal, and identify performance based on the situation and who is involved” (Elkins & Hanke, 2018, p. 35). Code switching allows students to respond to tensions between their class status and the perceived status of their institutional environment or between elements valued from their class background that conflict with their current or perceived class identity (Ardoin, 2018; Ardoin & martinez, 2019).…”
Section: Social Class Identity and Socializationmentioning
confidence: 99%